FOREIGN DIRECT INVESTMENTS AND REGIONAL DEVELOPMENT IN ROMANIA - CLAUDIA POPESCU (Revue Roumaine de Géographie)
After the year 2000, as business was improving and the flat tax was introduced, the positive perception of Romania by partners has attracted major capital flows in the national economy. Although industry is unanimously considered to be a major source of economic and social imbalance, yet in time it has proved to be by far more attractive to foreign investors than agriculture and tourism, which have a remarkable potential in this country. Major foreign investments are located in the main urban centres, because they are more easily accessible and more open to establishing relations and have a more dynamic economic milieu. Bucharest continues to hold a dominant position, either by hosting foreign companies, or simply their headquarters. Next come the regional capitals, basically cities with more than 300,000 inhabitants, with a large sphere of influence and capacity of coordinating the regional economic space. Moreover, present evolutions have shown that Romania is likely to loose its cheap labour advantage, a situation that makes its further attractiveness for international investment flows really questionable